Investigating the complex interplay between fibroblast activation protein α-positive cancer associated fibroblasts and the tumor microenvironment in the context of cancer immunotherapy - Kraxner, Anton; Braun, Franziska; Cheng, Wei-Yi; Yang, Tai-Hsien Ou; Pipaliya, Shweta; Canamero, Marta; Andersson, Emilia; Harring, Suzana Vega; Dziadek, Sebastian; Bröske, Ann-Marie E.; Ceppi, Maurizio; Tanos, Tamara; et al. (Frontiers in Immunology, 2024)
In our study, we explore the relationship between Fibroblast Activation Protein (FAP) expressing cancer-associated fibroblasts (FAP+CAF) and the tumor immune microenvironment. We focused on the analysis of immune cell subsets within FAP-rich and cytokeratin-negative (KRT-) stromal components. Our findings reveal distinct patterns of cellular composition and activity in different cancer types, which could play crucial roles in tumor infiltration and vasculature formation and the remodeling of the microenvironment. Furthermore, our research examined gene signatures related to stromal and immune cells, cytokine signaling and angiogenesis across various tumor types in relation to FAP expression. These investigations highlight both shared and unique biological aspects of a FAP+CAF dominated tumor microenvironment, offering new perspectives on tumor development and progression. The study underscores the dynamic interplay of stromal, immune and tumor cells in human tumors, accentuating the complexity of tumor biology and the necessity for personalized treatment and patient enrichment strategies.